The Synergistic Effect of Combination of Pentagamavunone-1 with Diosmin, Galangin, and Piperine in WiDr Colon Cancer Cells: In vitro and Target Protein Prediction - Muthi Ikawati; Hajidah Musyayyadah; Yurananda Magnalia Putri; Ummi Maryam Zulfin; Febri Wulandari; Dyaningtyas Dewi Pamungkas Putri; Edy Meiyanto (Universitas Gadjah Mada, 2023)
Pentagamavunone-1 (PGV-1) is a curcumin analog with a prominent anti-cancer potency in vitro and in vivo for several cancer types, including colon cancer. Combining PGV-1 with natural compounds such as diosmin, galangin, and piperine can enhance its effectiveness due to their promising chemoprevention properties. We aimed to evaluate the effectiveness of combining PGV-1 with diosmin, galangin, or piperine for colon cancer by using in vitro and bioinformatic approaches to predict their target proteins. WiDr cells were used as a model for colon adenocarcinoma (COAD). The cell viability under a single or combination treatment of PGV-1 and diosmin, galangin, or piperine was evaluated using direct counting by the trypan blue exclusion test. SwissTargetProtein, UALCAN, and OncoLnc were utilized to predict target proteins of the compounds in COAD, the expression level of target proteins in COAD, and the survival rate of patients with overexpressed target proteins, respectively. The IC50 values for PGV-1, diosmin, galangin, and piperine were 2.8´10-2 µg/mL, 81 µg/mL, 7 µg/mL, and 172 µg/mL, respectively. All the tested natural compounds showed synergistic effects when combined with PGV-1 at low concentrations. Eleven proteins that were overexpressed in COAD were identified as potential targets. Overlapped predicted targets of PGV-1 and galangin or piperine were CDK1, MET, and TOP2A. The high expression of another set of predicted target proteins, SCD, CA9, and SQLE, led to lower survival rates in COAD patients. We concluded that combinations of PGV-1 with natural compounds can synergistically enhane its anti-cancer activity for colon cancer.